“The Correlation Between The Students’ Self Regulation and Their English Learning Achievement of The Eleventh Grade at MAS TI Candung” - Nabila Nur Fajriah; Reflinda Reflinda; Melyan Melani; Veni Roza (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted since there were many problems that occur in students’ self regulation in studying English. The first problem is there were some of students had good self regulation in learning English, prepared well before learning, active in learning, pay attention when the teacher explained, and did the assignment that was given by the teacher. However the students’ English achievement was still low from standardization of minimum criteria. It means the some students have good self regulation, but low in English achievement. Second, some students did not have good self regulation in learning English, but their English achievements are good in. The students did not actively engaged in learnimg, they did not pay attention when the teacher explained the lesson, and they did not read the material before studying English, but their achievement in English were are good from standardization of minimum criteria. It means the students are low in self regulation, but their English achievements are good. This research aimed to know whether there is correlation between students’ self regulation and students’ English learning achievement in studying English.The design of this research was correlation research. Then, the instruments that used in this research were questionnaire for measuring students’ self-regulation and documentation in the form of the students’ mid-semester English test scores for measuring the students’ English learning achievement. The population of this research was all of the eleventh grade students of MAS-TI Candung in the academic year of 2021/2022 which consists of 5 classes. The sample was 30 students taken by simple random sampling technique. To find that self-regulation and English learning achievement have correlation or not, the researcher used Pearson Product Moment Correlation Coefficient. The finding of this research revealed that the coefficient (ρ) between students’ self-regulation and students’ English learning achievement was 0.690. It means, there is high correlation between students’ self-regulation and students’ English learning achievement. In other words, based on hypothesis testing, the t-score was 0.690 and t-table on α = 0.05 was 0.361. It means the t-score was higher than t-table. Hence, Ha was accepted and Ho was rejected which stated that there is a significant correlation between students’ self-regulation and students’ English learning achievement.